Intern Designed Modules for Conducting Potential Microgravity Solidification Experiments aboard the International Space Station - McElderry, Justin (Proceedings of the Wisconsin Space Conference, 2020)
MMaJIC (Microgravity Materials Joining Investigation Chamber) is a modular experiment chamber for performing materials science investigations. MMaJIC provides a controlled and sealed test environment for a wide variety of soldering and brazing experiment to examine porosity in microgravity. MMaJIC’s modular cartridge design includes a tray for housing the solder experiments and demonstrates simplicity to astronauts. SoLIDD (Solid Liquid Interface Directional Device) is a device for conducting directional solidification experiments which enables control of the microstructural development. SoLIDD has capability for varying temperature gradient and growth velocity. These quantities utilize heaters, coolers, and a directional drive unit. ICED-T (Interface Control Experiment with Directional Translation) is an apparatus that conducts directional solidification experiments of transparent materials which allows direct observation of the solid/liquid interface. Currently, it is in a breadboard phase that consists of the components mounted to a surface that allows the sample to be placed in an upright position. Orientation of the experiment (solid on the bottom, liquid on top) is important during testing ground samples to maintain stability. Ultimately, the goal of ICED-T is to conduct successful ground tests and then be configured to fit into an enclosure similar to MMaJIC and SoLIDD that could be utilized aboard the ISS.